Indirect moral governance in prostitution policy: How regulators incorporate stigmatized actors in intermediation processes - Eva-Maria Euchner; Nicolle Zeegers (Regulation & Governance, 2022)
Regulatory intermediaries have received attention in the analysis of different policy fields recently. Yet, their role in morality-based national governance arrangements is hardly addressed, neither is the question of how regulators incorporate stigmatized private actors. The current special issue contributes to closing this research gap by examining the three-party relationship between public regulators, private intermediaries, and targets in prostitution policy implementation. This introduction presents a typology of indirect moral governance, which is based on two dimensions: (1) the extent to which regulators perceive intermediaries as being trustworthy and (2) their operational capacities. Leveraging examples from the papers in the special issue, we elaborate on how the two dimensions lead to four forms of intermediation. Thus, the typology offers an innovative analytical tool to systematizes regulators' responses to governance and implementation problems in the case of morality policies and value-laden issues more generally, including the responsibilization of stigmatized actors.
Keywords: 330; implementation; morality policies; prostitution policy; regulatory intermediaries; responsibilization; trustworthiness